Nanoporous carbon materials for electrochemical sensing - Poh, Hwee Ling (2013)
Nanoporous carbon materials are highly important materials for a wide array of applications. Here we show that nanoporous carbon can act as highly active materials for electrochemical sensing. We observed that nanoporous carbon material exhibits a faster heterogeneous electron transfer than graphite and pure carbon nanotubes. Nanoporous carbon exhibits a superior electrochemical performance for sensing of important biomarkers such as dopamine, ascorbic acid, uric acid, NADH, DNA bases, and forensic-related compounds such as nitroaromatic explosives.